The Hellenistic City of Salamis, Greece - Chairetakis, Yannis (Journal of Hellenistic Pottery and Material Culture, 2022)
The city of Salamis »is situated in a bay on a spot of a peninsular form contiguous to Attica«. These are the words Strabo (geogr. 9, 1, 9) uses to define the location of the ancient city of Salamis in a bay of the island opposite Attica. The ancient city of Salamis, in the vicinity of the modern town of Ambelaki, is bounded on the north by the peninsula of Pounta and on the south by the oblong peninsula of Kynosoura (figs. 1–2). In antiquity, the sea extended less into the bay, and since then the rise of sea level by at least 1.50–2.00 m. has covered most of the structures once situated in the plain.